Analysis of Reduction Cost of Assembly Block Side Shell 1A (SS 1A) Using Critical Path Method (CPM) in Hospital Ship Project - Suharyoko; Baroroh, Intan (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Abstract The hospital ship project is a major project that has a long period of time, with limited space allocation and human resources as well. In order to avoid problems for PT XXX related to project completion, namely experiencing delays, where many factors affect the course of the project, an improvement analysis is needed for optimization. Optimization is done by scheduling a new project with the hope that in the next similar project PT XXX will not experience similar problems. Using Critical Path Method (CPM) analysis, the assembly process of Block Side Sheel 1A (SS 1A) on the Hospital Ship Project has a work network analysis with acceleration on activities E-F-G-J-K-L-M-N-S, through analysis steps using overtime. Thus it takes an acceleration cost of Rp. 6,943,510, or an additional cost of 32.26% of the initial cost to minimize the time from 64 days to 37 days, so that there is no delay in future hospital projects.